PHANGS-MeerKAT and MHONGOOSE HI observations of nearby spiral galaxies: physical drivers of the molecular gas fraction, Rmol - Eibensteiner, Cosima; Sun, Jiayi; Bigiel, Frank; Leroy, Adam K.; Schinnerer, Eva; Rosolowsky, Erik; Kurapati, Sushma; Pisano, D. J.; Blok, W. J. G. de; Barnes, Ashley T.; Thorp, Mallory; Colombo, Dario; et al. (Astronomy and astrophysics, 2024)
The molecular-to-atomic gas ratio is crucial to our understanding of the evolution of the interstellar medium (ISM) in galaxies. We investigated the balance between the atomic (ΣHI) and molecular gas (ΣH2) surface densities in eight nearby star-forming galaxies using new high-quality observations from MeerKAT and ALMA (for HI and CO, respectively). We defined the molecular gas ratio as Rmol = ΣH2/ΣHI and measured how Rmol depends on local conditions in the galaxy disks using multiwavelength observations. We find that, depending on the galaxy, HI is detected at > 3σ out to 20 − 120 kpc in galactocentric radius (rgal). The typical radius at which ΣHI reaches 1 M⊙ pc−2 is rHI ≈ 22 kpc, which corresponds to 1 − 3 times the optical radius (r25). We note that, Rmol correlates best with the dynamical equilibrium pressure, PDE, among potential drivers studied, with a median correlation coefficient of ⟨ρ⟩ = 0.89. Correlations between Rmol and the star formation rate surface density, total gas surface density, stellar surface density, metallicity, and ΣSFR/PDE (a proxy for the combined effect of the UV radiation field and number density) are present but somewhat weaker. Our results also show a direct correlation between PDE and ΣSFR, supporting self-regulation models. Quantitatively, we measured similar scalings as previous works, and attribute the modest differences that we do find to the effect of varying resolution and sensitivity. At rgal ≳ 0.4r25, atomic gas dominates over molecular gas among our studied galaxies, and at the balance of these two gas phases (Rmol = 1), we find that the baryon mass is dominated by stars, with Σ* > 5 Σgas. Our study constitutes an important step in the statistical investigation of how local galaxy properties (stellar mass, star formation rate, or morphology) impact the conversion from atomic to molecular gas in nearby galaxies.
Im Titel erscheint das "mol" tiefgestellt
Online verfügbar: 11. November 2024
Gesehen am 04.06.2025